2020
DOI: 10.1155/2020/8817843
|View full text |Cite
|
Sign up to set email alerts
|

Using Nonlinear Dynamics and Multivariate Statistics to Analyze EEG Signals of Insomniacs with the Intervention of Superficial Acupuncture

Abstract: Objective. As a noninvasive and nonpharmacological therapeutic approach, superficial acupuncture (SA) is a special method of acupuncture. In this study, using nonlinear dynamics and multivariate statistics, we studied the electroencephalography (EEG) of primary insomnia under SA intervention to investigate how brain regions change. Method. This study included 30 adults with primary insomnia. They underwent superficial acupuncture at the Shangen acupoint. The EEG signals were collected for 10 minutes at each st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that after superficial acupuncture treatment for patients with primary insomnia, the value of ApEn was lowered relative to in the resting state. 59 In another study, the MSE value decreased in people with insomnia symptoms during wakefulness and stage 1 of NREM sleep after experiencing beat frequency vibrations. 60 Interestingly, in the current study, we found that N3 may be more stable than other sleep stages.…”
Section: Changes In Objective Sleep In Gs Under Stress and Sr Effectsmentioning
confidence: 94%
“…It has been shown that after superficial acupuncture treatment for patients with primary insomnia, the value of ApEn was lowered relative to in the resting state. 59 In another study, the MSE value decreased in people with insomnia symptoms during wakefulness and stage 1 of NREM sleep after experiencing beat frequency vibrations. 60 Interestingly, in the current study, we found that N3 may be more stable than other sleep stages.…”
Section: Changes In Objective Sleep In Gs Under Stress and Sr Effectsmentioning
confidence: 94%
“…Shallow acupuncture can treat a variety of diseases, and its method of flattening, replenishing, and reducing is unique in the treatment of NAFLD. e principle of shallow acupuncture is to stimulate the meridian blood circulation through the physical stimulation of the meridian points by the needle tip, adjust the functional balance of the meridians and viscera, and play the role of strengthening the body, eliminating pathology and curing diseases [12,13]. is is basically the same as the principle of acupuncture treatment.…”
Section: Making Good Use Of Shallow Needlementioning
confidence: 99%
“…Therefore, real‐time scanning of brain areas during EAS is the best means to exclude interference by these factors. More recently, current acupuncture theory has suggested that changes in functional connectivity (FC) during acupuncture are dynamic (Qi et al., 2020 ). fMRI with simultaneous EAS may add relevant information to understand the effects of EAS as it more accurately represents the dynamic nature of the brain connectivity produced by EAS.…”
Section: Introductionmentioning
confidence: 99%